Tips and tricks for successful root canal treatment - Mat Daud, Muhamad Sharifuddin (2017)
How to maximise the outcome of root canal treatment? How to deal with curve root canal? How to deal with calcified canal? How to manage broken instrument? How to bypass ledge in root canal?